TINGKAT KEPATUHAN TENAGA KESEHATAN RUMAH SAKIT DALAM UPAYA PENCEGAHAN DAN PENULARAN CORONAVIRUS DISEASE 2019 - Lia Savira Febriani; Budiono Budiono; Hurun Ain (Jurnal Pendidikan Kesehatan, 2021)
Coronavirus disease 2019 or COVID 19 is a virus that is spreading in China with a very rapid rate of infection. According to WHO life report, the death toll from COVID 19 in Indonesia reached 12,000 people. Health care as a front end in hospital management should also optimize the performance of its duties according to established operational procedures. The purpose of this research is to explain the level of healthcare professional commitment to the prevention and transmission of coronavirus disease 2019 or COVID 19. The literature review search uses three electronic databases, namely PubMed, Scient direct and google scholar. The average number of respondents is 500 Responders. Articles selected by paying attention to the PEOS Framework then the articles analyzed one by one. Of the 10 articles analyzed, the results were articles that discussed handwashing obedience with n equal 7 and masking obedience with n equal 3. Ten articles were found that met the criteria of inclusiveness and exclusivity. Seven articles on health care compliance in hand washing and three articles on the use of masks with the highest level of compliance. In the COVID 19 pandemic, the level of health care compliance in the effort to wash hands and use face masks increases with the hand washing guidelines 7 moment in accordance with the WHO recommendation and using masks in accordance with the CDC guidelines